The Human Security Crisis in South Sudan: The Role of OCHA from 2019 to 2021 (Global Focus, 2022)
This study aims to analyze and explain the humanitarian crisis that occurred in South Sudan from 2019 to 2021, as a result of the protracted civil war, as well as the role of the Office For The Coordination Of Humanitarian Affairs (OCHA) in efforts to overcome and respond to the humanitarian crisis. In this study, the author uses several concepts and theories, which include the concept of Human Security, the concept of Responsibility to Protect, and the theory of International Organizations. The method used in this research is a descriptive qualitative method. The results showed that the humanitarian crisis that occurred in Sudan caused violations of several aspects of human security, which include personal security, community security, political security, economic security, food security, health security, and environmental security. Then in an effort to respond to and overcome the humanitarian crisis in South Sudan, OCHA did several things, namely making a policy agenda, providing information, advocating, and providing humanitarian funds for the humanitarian crisis in South Sudan.